Taguchi-Assisted Optimization Technique and Density Functional Theory for Green Synthesis of a Novel Cu-MOF Derived From Caffeic Acid and Its Anticancerious Activities - Malihe Zeraati (Frontiers Media S.A., 2021)
In this paper, we have reported an innovative greener method for developing copper-metal organic frameworks (Cu-MOFs) using caffeic acid (CA) as a linker extracted from Satureja hortensis using ultrasonic bath. The density functional theory is used to discuss the Cu-MOF-binding reaction mechanism. In order to achieve a discrepancy between the energy levels of the interactive precursor orbitals, the molecules have been optimized using the B3LYP/6–31G method. The Taguchi method was used to optimize the key parameters for the synthesis of Cu-MOF. FT-IR, XRD, nitrogen adsorption, and SEM analyses are used to characterize it. The adsorption/desorption and SEM analyses suggested that Cu-MOF has a larger surface area of 284.94 m2/g with high porosity. Cu-MOF has shown anticancer activities against the human breast cancer (MDA-MB-468) cell lines, and it could be a potent candidate for clinical applications.